1980
DOI: 10.1210/jcem-51-5-1058
|View full text |Cite
|
Sign up to set email alerts
|

A New Sensitive and Specific Bioassay for Lactogenic Hormones: Measurement of Prolactin and Growth Hormone in Human Serum*

Abstract: The replication of Nb 2 Node rat lymphoma cells in suspension culture is specifically stimulated by lactogenic hormones. Human (hPRL), ovine, bovine, and rat PRLs stimulated replication in a dose-dependent manner in the concentration range of 10 pg/ml to 1 ng/ml. Human, ovine, and bovine placental lactogens were similarly active. In addition, cell replication was stimulated by human GH (hGH), which is known to have lactogenic activity. Other hormones and growth factors examined were inactive. The growth stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
192
1
6

Year Published

1982
1982
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(207 citation statements)
references
References 22 publications
8
192
1
6
Order By: Relevance
“…Growth hormone produces effects in several culture systems (3, 11-13, 22, 30), but not with enough sensitivity and specificity to permit those systems to be used as an assay, except for primate growth hormone, whose prolactin activity can be assayed by using a prolactin-dependent cell line (35). It has recently been shown that growth hormone of several species promotes the adipose conversion of preadipose 3T3 mouse cells (23).…”
mentioning
confidence: 99%
“…Growth hormone produces effects in several culture systems (3, 11-13, 22, 30), but not with enough sensitivity and specificity to permit those systems to be used as an assay, except for primate growth hormone, whose prolactin activity can be assayed by using a prolactin-dependent cell line (35). It has recently been shown that growth hormone of several species promotes the adipose conversion of preadipose 3T3 mouse cells (23).…”
mentioning
confidence: 99%
“…The mechanism of action of prolactin on immune reactions is still obscure. The dependence of the Nb2 rat lymphoma on prolactin for its growth (22,23,25) suggests that this pituitary hormone may act directly on lymphocytes as a growth factor. However, indirect effects through organs that play key roles in immunity, such as the thymus or spleen, cannot yet be excluded.…”
mentioning
confidence: 99%
“…The biological activity of hormones produced in Pichia pastoris recombinant was determined by their ability to promote proliferation of the Nb2 cell line, which comes from rat lymphoma (54,55). GHs were also tested for their somatogenic activity in the adipocyte differentiation model based on the glyceraldehyde 3-phosphate dehydrogenase (GPDH) assay.…”
Section: Lactogenic Activity Bioassaymentioning
confidence: 99%